The Use of the Student Teams Achievement Divisions (STAD) Cooperative Learning Model to Improve Mastery of Qowa'id and Tarjamah - Heryana, Firman (Tadris Al-'Arabiyyah: Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2024)
Learning qowa'id for the majority of students is difficult, this phenomenon is faced by native Arabic speakers, another problem arises for foreign speakers, namely in translation. As one of the solutions to this problem, the author piloted a cooperative learning model of the STAD (Student Teams Achievement Divisions) type. So the purpose of this research is to find out the effectiveness or ineffectiveness of the learning model for increasing the mastery of qowa'id and tarjamah. This study uses a quantitative approach with a quasi-experimental research method in the form of a non-equivalent control group design. Through triangulation techniques for data collection, namely observation, tests and questionnaires. The population is all students of class IX MTs Husnul Khotimah Kuningan T.P. 2023-2024 and the sample is students of classes XI A and XI B. The test value data of the difference between the two mean post-testts of the experimental and control classes in increasing the mastery of qowa'id is the STAD-type cooperative learning model is effective for increasing qowaid mastery. And the test value data of the difference between the two average post-test of the experimental and control classes in increasing the mastery of tarjamah is the STAD type cooperative learning model is effective for increasing the mastery of tarjamah. So, this study is an additional reference for other similar research, that the STAD (Student Teams Achievement Divisions) type cooperative learning model is effective for increasing the mastery of qowa'id and tarjamah.